Iconic turns nation and religion in Eastern European cinema since 1989 - Berezhnaya, Liliya; Schmitt, Christian, 1978- (Leiden ; Boston : Brill, 2013)
After the epochal turn of 1989 a new wave of movies dealing with the complex entanglement of religious and national identity has emerged in in the eastern part of Europe. There has been plenty of evidence for a return of nationalism, while the predicated "return of religion(s)" is envisaged on a larger scale as a global phenomenon. The book suggests that in the wake of the historical turns of 1989, an "iconic turn" has taken place in Eastern Europe - in the form of a renewed cinematic commitment to make sense of the world in religious and/or national terms. 'Iconic Turns' combinestheoretical articles on the subject with case studies, bringing together researchers from different national backgrounds and disciplines, such as history, literary and film studies.
Introduction -- Religion and politics in Soviet and Eastern European cinema: a historical survey / Liliya Berezhnaya and Christian Schmitt -- Institutional Powers. Blessed films: the Russian Orthodox Church and patriotic culture in the 2000s / Hans-Joachim Schlegel -- Russian film premieres in 2010/11: sacralizing national history and nationalizing religion / Steven M. Norris -- A cinematic churchman: metropolitan Andrey Sheptytsky in Oles Yanchuk's Vladyka Andrey / Liliya Berezhnaya -- Sacred and profane images: rethinking history: heroes, saints and martyrs in contemporary Russian cinema. The godless Czechs? cinema, religion and Czech national identity / Eva Binder -- Beyond the surface, beneath the skin: immanence and transcendence in Gyorgi Palfi's films / Jan Culik -- Conflict, trauma, and memory. Narrating the Shoah in Poland: post-1989 movies about Polish-Jewish relations in times of German extermination politics / Christian Schmitt -- Memory, national identity, and the cross: Polish documentary films about the Smolensk plane crash / Maren Roger -- Religion visible and invisible: the case of post-Yugoslav anti-war films / Miroslaw Przylipiak.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Motion pictures -- Europe, Eastern; Religion in motion pictures; National characteristics in motion pictures; ART / Film & Video; PERFORMING ARTS / Film & Video / Reference; Electronic books